Предмет: Алгебра,
автор: Аноним
Упростите выражение
(a^-2-b^-2)^-1:(a-b)^-1
Ответы
Автор ответа:
0
(a⁻² - b⁻²)⁻¹ /(a - b)⁻¹ = [1/(1/a² - 1/b²)] / (1/(a-b)) = [1/((b²-a²)/(a²b²)) × (a-b) =
= (a-b)a²b²/(b²-a²) = -(a-b)a²b²/((a-b)(a+b)) =
=-a²b²/(a+b)
= (a-b)a²b²/(b²-a²) = -(a-b)a²b²/((a-b)(a+b)) =
=-a²b²/(a+b)
Автор ответа:
0
Спасибо вам)))
Автор ответа:
0
не за что..)) обращайтесь, если что.
Похожие вопросы
Предмет: ОБЖ,
автор: nikolechernobay
Предмет: Информатика,
автор: polina25816
Предмет: Физика,
автор: 45530609
Предмет: Алгебра,
автор: бубончик1